Endocan expression and correlation with other endothelial determinants in developing a score for early identification of diabetic peripheral neuropathy - Prajna Parimita Jena; Rachita Nanda; Amritava Ghosh; Suprava Patel; Seema Shah; Eli Mohapatra (Scientific Reports)
Abstract Diabetic peripheral neuropathy is a common complication of diabetes mellitus that has dire outcomes, affecting the economic profile of a country. Despite the multifactorial background of the pathogenesis of this disease, the mechanism underlying peripheral neuropathy is still unclear. Endothelial damage is a new determinant of pathogenesis, with endocan as a potential biomarker for endothelial dysfunction in diabetic peripheral neuropathy patients. In this cross-sectional study, with 49 patients with diabetes with peripheral neuropathy and 48 patients with diabetes without neuropathy, endothelial biomarkers such as endocan, hs-CRP, vitamin D, and lipid profiles were measured and analyzed in both groups. The standardized scores for dyslipidemia, inflammation, vitamin D and endocan were calculated. All of these biomarkers were significantly altered in peripheral neuropathy patients. A strong correlation between endocan levels and lipid profiles and between hs-CRP and vitamin D levels was detected. The inflammatory score and a combined score including all the above biomarkers might help in the early stratification of diabetic patients who are at greater risk of developing peripheral neuropathy.